More Talk, Less Need for Monitoring: Communication and Deterrence in a Public Good Game. Issue 2 (26th December 2017) - Kingsley, David C.; Muise, Daniel
Abstract: This paper investigates the impact of communication in a public good game with a central authority. The central authority includes a fixed cost that increases with the level of monitoring which in turn determines the level of deterrence. The level of monitoring is both exogenously and endogenously determined. Across three treatments subjects either have no opportunity to communicate, communicate only when the level of monitoring is exogenously imposed, or communicate only when the level of monitoring is endogenously selected. Results suggest that, in both treatments, average earnings are significantly higher with the opportunity to communicate. Most significantly, with the opportunity to communicate prior to endogenous selection, groups practically eliminate monitoring (imposing a low cost, non-deterrent, central authority), while maintaining a high level of contributions. Communication appears to make groups less dependent on institutional deterrence and allows them to reduce the costs of central authority.